An economic and environmental assessment of a glyphosate ban for the example of maize production. (5th February 2019) - Böcker, Thomas; Britz, Wolfgang; Möhring, Niklas; Finger, Robert
Abstract: We aim to contribute to a more informed discussion of the economic and environmental effects of a glyphosate ban in European agriculture. As real-world observations of weed control under a glyphosate ban are not available, we develop a normative modelling approach based on damage abatement functions considering production risk and farmers' risk preferences. Different sources of risk are included by incorporating uncertainty of both attainable yield level and weed pressure. Results for a case study of silage maize cultivation in 377 municipalities in North Rhine-Westphalia, Germany, show that a glyphosate ban causes a shift towards more mechanical weed control, but not to more pronounced use of selective herbicides. The ban slightly reduces net profits and yields, leads to a significant reduction of the overall toxicity of pesticide use, but increases energy consumption of the agricultural system. The magnitude of these effects is found to be critically dependent on output price levels and yield expectations.